A conceptual investigation of justice - Johannsen, Kyle (Routledge innovations in political theory, 2018)
In this book, [the author] calls for renewed attention to the manner in which the word 'justice' is and should be used. Focusing on the late work of G.A. Cohen, [the author] argues that debates over both the content and scope of egalitarian justice are, to a large extent, really just conceptual. Doing so sheds light on the nature of both democracy and legitimacy, and, paradoxically, makes better sense of the idea that justice is 'the first virtue of institutions.